Spojrzenie w przeszłość. O nurcie tzw. "późnej narracji archeologicznej" w dwudziestowiecznej polskiej literaturze fantastycznonaukowej - Mazurkiewicz, Adam (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2005)
The category of late archeological narrative, related to science-fiction, is distingushed due to thematic criterion. The plot is based on a motif of excavations. The heroes, situated in distant future, are usually research workers, studying the lost civilisation. However, they have nothing but excavation for their research, because of discontinuity of culture, due to the erlier great dissaster (for instance the total war). This is why their investigation turns out to be vain: the argumentation is correct, but deduction is false, that is obvious for a learner. The learner can easily recognize the lost civilisation, the subject of research in the presented world, as his own contemporaneousness. Late archeological narrative is a kind o f mental experiment, that presents limitations of science and of human capibility to make the past known. There are few novels in Polish literature, representing this trend; in my opinion, it hasen’t exhausted its artistic possibilities yet.